A Comprehensive Bibliometric Analysis of Research Trends About Congenital Toxoplasmosis. - Bağcı, Mustafa; Bağcı, Özlem Ulusan (Turkish Journal of Parasitology / Türkiye Parazitoloji Dergisi, 2024)
Objective: Toxoplasma gondii is an obligate intracellular protozoon that infects approximately one-third of the human population. The parasite could transmit from mother to fetus in cases of acute infection during pregnancy and cause complications in the fetus. The bibliometric analysis is a popular research area that evaluates all the studies indexed in particular databases on a subject. Methods: This article puts forth bibliometric review of the literature on maternal and congenital toxoplasmosis research indexed in the Web of Science database between 1945 and 2024. VOS viewer, Web of Science and MS Office Excel 17 programs were used in the study. Results: The results of the search showed 1476 publications. The countries that most contributed to the literature were France (n=306, 20.73%), the USA (n=229, 15.52%), and Brazil (n=146, 9.89%). The most cited country was also France (n=10271, 35.52%), followed by the USA (n=9113, 31.51%), and England (n=2611, 9.03%). The top three countries by number of citations per document were Denmark (44.88), the USA (39.79) and France (33.57). The five departments with the most publications are Pediatrics (20.26%), General Internal Medicine (18.16%), Infectious Diseases (16.8%), Obstetrics (14.57%), and Immunology (11.86%). Wallon M. (n=57), Peyron F. (n=49), Thulliez P. (n=36) and Vilena I. (n=36) were the leading authors in terms of contribution to the literature. The five most published journals were Pediatric Infectious Disease Journal (3.66%), Journal of Clinical Microbiology (2.78%), Lancet (2.3%), Presse Medicale (1.76%), and American Journal of Obstetrics and Gynecology (1.63%). Conclusion: France is one of the countries that pays the most attention to congenital toxoplasmosis and compatible with this, in our study, the country with the highest number of studies on congenital toxoplasmosis was France. It is thought that drawing more attention to this issue and conducting more studies in countries where the disease is common might yield successful results, as in France.